Wilhelm Schulthess, Pioneer in the Treatment of Spinal Deformities: The Testimony of the Rizzoli Orthopedic Institute. Issue 5 (1st March 2019) - Mazzotti, Antonio; Tomba, Patrizia; Perna, Fabrizio; Stefanini, Niccolò; Viganò, Anna; Faldini, Cesare
Abstract : N/A: Wilhelm Schulthess was a pioneer in the treatment of spinal deformities. The Rizzoli Orthopedic Institute in Bologna, Italy, awarded him in 1911 for his work: "pathology and treatment of spinal deformities". In this paper the Swiss Clinician is remembered through the documentation still preserved at the Rizzoli institute. Abstract : Wilhelm Schulthess was a pioneer in the treatment of spinal deformities. The Rizzoli Orthopedic Institute in Bologna, Italy, awarded him in 1911 for his work: " pathology and treatment of spinal deformities ". In this article the Swiss Clinician is remembered through the documentation still preserved at the Rizzoli Institute.